Experimental Measurement of Deposition Chloride Ions in the Vicinity of Road Cut - Vacek, Miroslav; Křivý, Vít; Kreislová, Kateřina; Vlachová, Markéta; Kubzová, Monika (Materials (Basel, Switzerland), 2022)
Chloride ions are nowadays the main cause of the degradation of steel and reinforce concrete construction in the vicinity of the road. On the other hand, chloride ions, usually in the form of de-icing salts or brine, are very important for safe winter traffic on the roads. This creates a slightly schizophrenic situation where it is necessary to ensure safe traffic in the winter period and at the same time to affect the service life of the structure as little as possible. The effect of the roadway on chloride deposition is a long-studied, but still imprecisely understood, part of the effect of chloride ions on structures in the vicinity of the roadway. This paper discusses the experimental measurement of chloride deposition in the vicinity of the I/11 road in the Czech Republic by dry plate method, wet candle method and corrosion coupons. Statistical analysis of correlation and regression is performed on the results of measurements by wet candle and horizontal dry plate methods. The methods are interdependent. A detailed analysis of the surface and chemical properties of the corrosion products is performed on the corrosion coupons. Using the corrosion loss, the environmental category C2 is determined. Observation of the microclimate in the vicinity of the roads gives to engineers a basis for the correct design of structures around the roads. The conclusions of the experimental measurements are intended to help engineers to design a structure that is safe, serviceable and sufficiently resistant to chloride ions within its service life.
Keywords: reinforce concrete; bridge; wet candle method; rust; steel; corrosion coupon; dry plate method; road; chloride